The safety and effectiveness of adenosine diphosphate receptor inhibitor pretreatment among acute myocardial infarction patients treated with percutaneous coronary intervention in community practice: Insights from the TRANSLATE‐ACS study. Issue 2 (8th October 2017) - Effron, Mark B.; Wang, Tracy Y.; Fonarow, Gregg C.; Henry, Timothy D.; Zettler, Marjorie E.; Baker, Brian A.; McCoy, Lisa A.; Peterson, Eric D.
Abstract: Objectives: To understand the optimal timing of adenosine diphosphate (ADP) receptor inhibitor pretreatment prior to percutaneous coronary intervention (PCI) among acute myocardial infarction (MI) patients. Background: The role of ADP receptor inhibitor pretreatment in this population is unclear. Methods: A total of 9, 251 ADP receptor inhibitor‐naïve MI patients undergoing PCI at 229 TRANSLATE‐ACS sites were evaluated. Adjusted risks of in‐hospital major adverse cardiovascular events (MACE) and major bleeding were compared among patients with and without pretreatment using inverse probability‐weighted propensity adjustment. Results: Of 9, 251 patients treated with either prasugrel or clopidogrel during the index MI hospitalization, 4, 056 (44%) received pretreatment (ST‐segment elevation MI [STEMI] 54.9%, non‐STEMI 45.1%); pretreatment was used more commonly among those receiving clopidogrel than prasugrel (52% vs. 20%, P  < 0.0001). MACE risks were not significantly different between patients with and without pretreatment (clopidogrel 2.1% vs. 2.2%, adjusted hazard ratio [HR] 1.00, 95% confidence interval [CI] 0.70–1.43; prasugrel 2.1% vs. 2.3%, adjusted odds ratio [OR] 0.82, 95% CI 0.42–1.60). No differences in major bleeding were observed among those receiving versus not receiving pretreatment (clopidogrel 3.1% vs. 3.5%, adjusted HR 0.94, 95% CI 0.65–1.36; prasugrel 2.5% vs. 2.7%, adjusted OR 0.93, 95% CI 0.42–2.02); results were similar when stratified by MI type. Conclusions: ADP receptor inhibitor pretreatment (44%) is commonly used among acute MI patients undergoing PCI in contemporary practice, but no significant differences were found in in‐hospital MACE and/or bleeding risks between patients receiving versus not receiving pretreatment, regardless of ADP receptor inhibitor type.